How to Assess the Benefits of Nonperforming Loan Disposal in Sub-Saharan Africa Using a Simple Analytical Framework - Bunda, Irina; Eyraud, Luc.; Wang, Zhangrui.. (Washington, D.C. : International Monetary Fund, 2021)
The coronavirus (COVID-19) crisis, which has hit financial systems across Africa, is likely to deteriorate banks' balance sheets. The largest threat to banks pertains to their loan portfolios, since many borrowers have faced a sharp collapse in their income, and therefore have difficulty repaying their obligations as they come due. This could lead to a sharp increase in nonperforming loans (NPLs) in the short to medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Foreign Exchange; Informal Economy; Underground Econom